The market for corporate control: two models under review. Spain vs Ireland - Alcalde Fradejas, Nuria (Papeles de Europa, 2021)
In this paper, we present a comparative study of merger and acquisitions of listed companies in two countries, Spain and Ireland, representatives of the two different corporate governance models that coexist in Europe. The analysis carried out using the information on deals announced during the 1993-2016 period, reveals greater activity and internationalization of the Irish market for corporate control, a greater importance of minority acquisitions in Spain, higher premiums paid to shareholders in Ireland, and differences between the profiles of the companies acquired in both countries. These differences do not seem to have been reduced over time as a consequence of the greater process of economic integration and legislative harmonization in the European Union.
Keywords: Mergers and acquisitions; corporate governance; Europe